A Rare Case of Gastrointestinal Tract Foreign Body; Glassy Stomach - Ebrahimi, Mohsen; Malmir, Jafar; Mahmoudi Gharaee, Azadeh; Foroughian, Mahdi (Archives of Academic Emergency Medicine, 2017)
Ingestion of foreign bodies is common and conservative treatment can eliminated most particlesfrom the gastrointestinal tractunless peritoneal signs appear. A 22-year-old man presented to emergency department who had ingested glass particles of a crushed beverage bottle. He complained of epigastric and periumbilical pain. Physical examination did not revealany peritoneal signs. Abdominal X-ray showed stomach full of small glass particles. Conservative treatment, without any surgical intervention,resulted insafely eliminating glass particlesin this patient.